Measuring changes in women's empowerment and its relationship to intimate partner violence. Issue 5 (4th July 2018) - Schuler, Sidney; Field, Samuel; Bernholc, Alissa
ABSTRACT: This article uses survey data to examine changes over time in the relationship between women's empowerment and intimate partner violence (IPV) in six Bangladeshi villages. Prior analyses using a limited set of empowerment indicators available in both 2002 and 2014 suggested a persistent positive association between empowerment and IPV. The article's analysis, using an updated set of measures derived from extensive qualitative studies, suggests that empowerment may be shifting from a risk factor for IPV to a protective factor. The article discusses the methodological limitations posed by the shifting manifestations of empowerment and its social meanings within and across settings.